TiO2 (at) SiO (at) Si / RGO silicon-based negative electrode material and preparation method and application thereof
By double-layer coating of SiO and TiO2 on the Si core, and even anchoring TiO2@SiO@Si particles on the RGO, the TiO2@SiO@Si/RGO silicon-based anode material is formed, and the volume expansion and interface of the silicon-based anode material are solved. The problem of resistance significantly improves its electrochemical properties.
Patent Information
- Application Number
- CN202411600721.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing silicon-based anode materials have poor circulation and rate performance due to volume expansion in lithium-ion batteries, and have high interface resistance, which limits their energy density and electrochemical properties.
Using TiO2@SiO@Si/RGO silicon-based anode material, SiO and TiO2 are double-layered coated by sol-gel method, and TiO2@SiO@Si particles are uniformly anchored on RGO with a three-dimensional framework structure. Form a stable composite structure.
It effectively suppresses the volume expansion of the silicon-based negative electrode material, reduces the interface resistance, and improves the rate performance, first-effect performance and cycling performance.
Smart Images

Figure CN119480982A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium battery negative electrode materials, and specifically relates to a TiO2@SiO@Si / RGO silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, the commonly used negative electrode materials on the market are graphite-based negative electrode materials. The high-end graphite synthesized by existing technology can reach a capacity of 360-365mAh / g, which is very close to the theoretical capacity of 372mAh / g, but it can no longer meet people's needs for higher energy density. The theoretical capacity of silicon (Si) negative electrode materials at room temperature is 3580mAh / g, and the theoretical capacity at high temperature is 4200mAh / g, which is nearly ten times the theoretical value of graphite materials. Silicon negative electrode materials have the advantages of being environmentally friendly, having a low lithium insertion and extraction potential (0.4V), and being rich in resources. However, silicon has a serious volume expansion (>300%) during the charging and discharging process, which causes the electrode material to rupture or even pulverize, causing the SEI film on the surface of the silicon negative electrode to continuously rupture and form, consuming a large amount of electrolyte and active Li + , increasing the polarization of the electrode, leading to extremely poor cycle performance. The huge volume change will also lead to the loss of electrical contact between particles or between particles and current collectors, causing the active material to fall off from the current collector. At the same time, its own poor conductivity will also restrict its development.
[0003] In response to the above problems, the modification research of Si negative electrode mainly includes the development of nano-silicon of different dimensions, carbon coating, silicon oxide materials, silicon oxide coating, Si / metal alloys, and conductive additives, electrolytes and binders for supporting Si negative electrode. However, although the above methods can improve the volume expansion of Si negative electrode to a certain extent, they have certain limitations in improving the rate performance, cycle performance, first efficiency, etc. of Si negative electrode. Summary of the invention
[0004] In view of the problem that the existing silicon-based negative electrode materials have poor rate performance, the present invention provides a TiO2@SiO@Si / RGO silicon-based negative electrode material and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the TiO2@SiO@Si / RGO silicon-based negative electrode material comprises RGO having a three-dimensional skeleton structure and TiO2@SiO@Si particles composited on the RGO; the TiO2@SiO@Si particles comprise a Si core and a SiO layer coated on the surface of the Si core and a TiO2 layer coated on the surface of the SiO.
[0006] In a preferred embodiment, the Si core contains at least one Si particle.
[0007] In a preferred embodiment, the D50 particle size of the Si particles is 0.05-5 μm.
[0008] In a preferred embodiment, the mass ratio of the RGO to the TiO2@SiO@Si particles is (0.5-2):100.
[0009] In a preferred embodiment, the molar ratio of SiO to Si in the TiO2@SiO@Si particles is (0.9-1.2):1.
[0010] In a preferred embodiment, the mass fraction of TiO2 in the TiO2@SiO@Si particles is 20-25wt%.
[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned TiO2@SiO@Si / RGO silicon-based negative electrode material, the preparation method comprising the following steps:
[0012] S1. Silicon powder, a silicate compound, water, and an organic solvent I are mixed and treated under alkaline conditions to obtain a SiO@Si precursor material, and the SiO@Si precursor material is subjected to a first calcination treatment to obtain SiO@Si particles including a Si core and a SiO layer coated on the surface of the Si core;
[0013] S2. Mixing SiO2@Si particles, titanate compounds, organic solvent II, and an acidic substance to obtain a mixture A, mixing water with the organic solvent III to obtain a solution B, and then mixing the mixture A with the solution B and performing a sol-gel reaction, and obtaining a TiO2@SiO2@Si precursor material after separation and drying;
[0014] S3. The TiO2@SiO@Si precursor material, graphene oxide dispersion and reducing agent are mixed and subjected to oxidation-reduction reaction, and then the obtained TiO2@SiO@Si / RGO hydrogel precursor is freeze-dried and then the obtained TiO2@SiO@Si / RGO aerogel precursor is subjected to a second calcination treatment to obtain the TiO2@SiO@Si / RGO silicon-based negative electrode material.
[0015] In a preferred embodiment, in step S1, the molar ratio of the silicon powder to the silicate compound is 1:(0.9-1.2).
[0016] In a preferred embodiment, in step S1, the alkaline condition includes a pH of 8-9.
[0017] In a preferred embodiment, in step S2, the mass ratio of the SiO@Si particles to the titanate compound is 1:(1-1.4).
[0018] In a preferred embodiment, in step S2, the acidic substance is used in an amount such that the pH of the mixture A is 3-6.
[0019] In a preferred embodiment, in step S3, the mass ratio of the TiO2@SiO@Si precursor material to graphene oxide is 100:(0.5-2).
[0020] In a preferred embodiment, in step S3, the concentration of the graphene oxide dispersion is 2.5-6 mg / mL.
[0021] In a preferred embodiment, in step S3, the mass ratio of the graphene oxide to the reducing agent is 1:(0.2-2.5).
[0022] In a preferred embodiment, the conditions of the first calcination treatment include: a temperature of 900 to 1100° C. and a time of 2 to 4 hours.
[0023] In a preferred embodiment, the conditions of the second calcination treatment include: a temperature of 400-500° C. and a time of 1-2 hours.
[0024] In a preferred embodiment, the sol-gel reaction time is 1 to 3 hours.
[0025] In a preferred embodiment, the sol-gel reaction further includes an aging step of 20 to 28 hours.
[0026] In a preferred embodiment, the conditions of the oxidation-reduction reaction include: a temperature of 90 to 180° C. and a time of 6 to 12 hours.
[0027] In a preferred embodiment, the D50 particle size of the silicon powder is 0.05-5 μm.
[0028] In a preferred embodiment, the silicate compound is at least one selected from tetraethyl orthosilicate, tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate.
[0029] In a preferred embodiment, the titanate compound is selected from at least one of tetraethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium isooctylate and titanium acetylacetonate.
[0030] In a preferred embodiment, the organic solvent I, organic solvent II and organic solvent III are each independently selected from at least one of n-butanol, isobutanol and ethanol.
[0031] In a preferred embodiment, the reducing agent is selected from at least one of sodium bisulphite formaldehyde, sodium sulfide, ascorbic acid, hydrogen iodide and hydroquinone.
[0032] In a third aspect, the present invention also provides the application of the above-mentioned TiO2@SiO@Si / RGO silicon-based negative electrode material in lithium-ion batteries.
[0033] The key to the present invention is to design and synthesize a TiO2@SiO@Si / RGO silicon-based negative electrode material with a specific structure. First, the Si core is double-coated with SiO and TiO2 in sequence by a sol-gel method. The structure gradually enhances the ability to inhibit the volume expansion of Si from the inside to the outside. SiO and TiO2 are bonded by Si-O-Ti chemical bonds, and the structure is more stable and is conducive to reducing the interface resistance. Secondly, TiO2@SiO@Si particles are uniformly anchored on RGO with a three-dimensional skeleton structure by forming Ti-OC chemical bonds. The obtained TiO2@SiO@Si / RGO silicon-based negative electrode material has a double-layer coating of SiO and TiO2 and a three-dimensional skeleton structure, which can not only effectively inhibit the volume expansion of the silicon-based negative electrode material when used in a lithium-ion battery, but also promote the transfer of ions, thereby improving its rate performance and first-efficiency performance. In addition, since the SiO and TiO2 coating layers are bonded through Si-O-Ti chemical bonds and the TiO2@SiO@Si particles and RGO are bonded through Ti-OC chemical bonds, the TiO2@SiO@Si / RGO silicon-based anode material has a stable structure and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the SEM image of the TiO2@SiO@Si / RGO silicon-based negative electrode material obtained in Example 1.
[0035] Figure 2 This is the TEM image of the TiO2@SiO@Si / RGO silicon-based negative electrode material obtained in Example 1.
[0036] Figure 3 This is the TEM image of the TiO2@SiO@Si particles obtained in Example 1. DETAILED DESCRIPTION
[0037] The TiO2@SiO@Si / RGO silicon-based negative electrode material provided by the present invention comprises RGO with a three-dimensional skeleton structure and TiO2@SiO@Si particles composited on the RGO. The TiO2@SiO@Si particles comprise a Si core, a SiO layer coated on the surface of the Si core, and a TiO2 layer coated on the surface of the SiO.
[0038] In the present invention, the Si core preferably contains one or more Si particles. The D50 particle size of the Si particles is preferably 0.05 to 5 μm, such as 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value therebetween. The term "D50 particle size" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%.
[0039] In the present invention, the mass ratio of the RGO to the TiO2@SiO@Si particles is preferably (0.5-2):100, such as 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100 or any value therebetween. Within the above preferred range, it is more conducive to uniformly distributing the TiO2@SiO@Si particles on the RGO while ensuring the formation of a three-dimensional network structure, thereby being more conducive to improving the rate performance, first-efficiency performance and cycle performance of the TiO2@SiO@Si / RGO silicon-based negative electrode material.
[0040] In the present invention, the molar ratio of SiO to Si in the TiO2@SiO@Si particles is preferably (0.9-1.2):1, such as 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1 or any value therebetween. This is more conducive to complete SiO coating of Si and inhibiting the volume expansion of Si.
[0041] In the present invention, the mass fraction of TiO2 in the TiO2@SiO@Si particles is preferably 20-25wt%, such as 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt% or any value therebetween. Within the above preferred range, it is more conducive to ensuring the complete coating of the SiO@Si main material by TiO2, further inhibiting the volume expansion of Si, and improving the electrochemical properties of the material.
[0042] The preparation method of the TiO2@SiO@Si / RGO silicon-based negative electrode material provided by the present invention comprises the following steps:
[0043] S1. Silicon powder, a silicate compound, water, and an organic solvent I are mixed and treated under alkaline conditions to obtain a SiO@Si precursor material, and the SiO@Si precursor material is subjected to a first calcination treatment to obtain SiO@Si particles including a Si core and a SiO layer coated on the surface of the Si core;
[0044] S2. Mixing SiO2@Si particles, titanate compounds, organic solvent II, and an acidic substance to obtain a mixture A, mixing water with the organic solvent III to obtain a solution B, and then mixing the mixture A with the solution B and performing a sol-gel reaction, and obtaining a TiO2@SiO2@Si precursor material after separation and drying;
[0045] S3. The TiO2@SiO@Si precursor material, graphene oxide dispersion and reducing agent are mixed and subjected to oxidation-reduction reaction, and then the obtained TiO2@SiO@Si / RGO hydrogel precursor is freeze-dried and then the obtained TiO2@SiO@Si / RGO aerogel precursor is subjected to a second calcination treatment to obtain the TiO2@SiO@Si / RGO silicon-based negative electrode material.
[0046] In the specific preparation process of the above silicon-based negative electrode material, in step S1, the mixing order and method of the silicon powder, silicate compound, water, and organic solvent I are not specifically limited. They can be added together and mixed at the same time, or some components can be mixed first and then the remaining components are added and mixed. Preferably, the silicate compound, water, and organic solvent I are mixed and then ultrasonically treated for 20 to 40 minutes, and the silicon powder is added and then ultrasonically treated for 20 to 40 minutes. The resulting mixture is evaporated under alkaline conditions to dry the solvent, and the resulting powder is the SiO@Si precursor material.
[0047] In the present invention, in step S1, the molar ratio of the silicon powder to the silicate compound is preferably 1:(0.9-1.2), such as 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1 or any value therebetween. The alkaline conditions include a pH preferably of 8-9, such as 8, 8.2, 8.5, 8.8, 9 or any value therebetween, and the growth rate of the particles is controlled by regulating the pH value of the alkaline conditions, thereby controlling the size of the particles. At this time, controlling the pH to 8-9 is more conducive to obtaining SiO@Si precursor material particles of uniform size. The alkaline conditions can be achieved by adding one of the alkaline substances such as ammonia water, sodium hydroxide, potassium hydroxide, etc., and the amount of the alkaline substance added is preferably such that the pH of the reaction system is 8-9. The amount of the silicate compound is preferably 5.5-6.2 wt% of the total mass of the mixture, such as 5.5 wt%, 5.8 wt%, 6 wt%, 6.1 wt%, 6.2 wt% or any value therebetween.
[0048] In the specific preparation process of the above-mentioned silicon-based negative electrode material, in step S2, the mixing order and method of the SiO@Si particles, titanate compounds, organic solvent II, and acidic substances are not specifically limited. They can be added together and mixed at the same time, or some components can be mixed first and then the remaining components are added and mixed. Preferably, the organic solvent II and the acidic substance are mixed first, and then the SiO@Si particles and titanate compounds are added, and the mixture A is obtained after stirring evenly.
[0049] In the present invention, in step S2, the mass ratio of the SiO@Si particles to the titanate compound is preferably 1:(1-1.4), such as 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or any value therebetween, which is more conducive to ensuring the complete coating of the SiO@Si main material by TiO2 within the preferred range, further inhibiting the volume expansion of Si, and improving the electrochemical properties of the material. The amount of the acidic substance is preferably such that the pH of the mixture A is 3-6, such as 3, 4, 5, 6 or any value therebetween. The effect of controlling the pH to 3-6 is to prevent the titanate compound in the mixture A from hydrolyzing. The acidic substance is preferably at least one of nitric acid, hydrochloric acid, hydrofluoric acid, and citric acid. The amount of the titanate compound is preferably 5-8wt% of the total mass of the mixture A, such as 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt% or any value therebetween.
[0050] In the specific preparation process of the above silicon-based negative electrode material, step S3 can be specifically as follows: first, the TiO2@SiO@Si precursor material, graphene oxide dispersion, and reducing agent are mixed and stirred for 1 to 3 hours to obtain a uniform mixed solution, and then transferred to a Teflon-lined stainless steel autoclave for oxidation-reduction reaction, and the obtained TiO2@SiO@Si / RGO hydrogel precursor is freeze-dried to obtain a TiO2@SiO@Si / RGO aerogel precursor, and then a second calcination treatment is performed to obtain a TiO2@SiO@Si / RGO silicon-based negative electrode material. Among them, the TiO2@SiO@Si / RGO hydrogel precursor can also be purified and impurity-removed before freeze-drying.
[0051] In the present invention, in step S3, the mass ratio of the TiO2@SiO@Si precursor material to graphene oxide (GO) is preferably 100:(0.5-2), such as 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100, 2:100 or any value therebetween. The concentration of the graphene oxide dispersion is preferably 2.5-6 mg / mL, such as 2.5 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL or any value therebetween. The mass ratio of the graphene oxide to the reducing agent is preferably 1:(0.2-2.5), such as 1:0.2, 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5 or any value therebetween, which is more conducive to the formation of RGO with a three-dimensional skeleton structure and the composite of TiO2@SiO@Si particles and RGO, thereby improving the rate performance, first-efficiency performance and cycle performance of the TiO2@SiO@Si / RGO silicon-based negative electrode material.
[0052] In the present invention, the conditions of the first calcination treatment may specifically include: the temperature is preferably 900-1100°C, such as 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value therebetween; the time is preferably 2-4h, such as 2h, 2.5h, 3h, 3.5h, 4h or any value therebetween.
[0053] In the present invention, the conditions of the second calcination treatment include: a temperature of 400-500°C, such as 400°C, 420°C, 450°C, 480°C, 500°C or any value therebetween; a time of 1-2h, such as 1h, 1.2h, 1.5h, 1.8h, 2h or any value therebetween. At this time, it is more conducive to the formation of anatase TiO2 and the removal of impurity elements such as O and H in RGO, thereby improving the rate performance, first-efficiency performance and cycle performance of TiO2@SiO@Si / RGO silicon-based negative electrode materials. The first calcination treatment and the second calcination treatment are preferably carried out under an inert atmosphere, and the inert atmosphere is preferably at least one of nitrogen, argon, helium and xenon.
[0054] In the present invention, the sol-gel reaction time is preferably 1 to 3 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any value therebetween. The sol-gel reaction is preferably followed by an aging step, and the aging time is generally 20 to 28 hours, such as 20 hours, 22 hours, 24 hours, 25 hours, 26 hours, 28 hours or any value therebetween.
[0055] In the present invention, the conditions of the oxidation-reduction reaction may specifically include: the temperature is preferably 90-180°C, such as 90°C, 100°C, 120°C, 150°C, 180°C or any value therebetween; the time is preferably 6-12h, such as 6h, 8h, 10h, 12h or any value therebetween.
[0056] In the present invention, the D50 particle size of the silicon powder is preferably 0.05 to 5 μm, such as 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value therebetween.
[0057] In the present invention, specific examples of the silicate compounds include, but are not limited to, at least one of tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate.
[0058] In the present invention, specific examples of the titanate compounds include, but are not limited to, at least one of tetraethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium isooctylate and titanium acetylacetonate.
[0059] In the present invention, the organic solvent I, organic solvent II and organic solvent III are each independently selected from at least one of n-butanol, isobutanol and ethanol.
[0060] In the present invention, specific examples of the reducing agent include, but are not limited to, at least one of sodium bisulfite formaldehyde, sodium sulfide, ascorbic acid, hydrogen iodide and hydroquinone.
[0061] The present invention will be described in detail below through specific embodiments.
[0062] The GO in the following examples and comparative examples was purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, with the product number TNIRGO (industrial grade graphene).
[0063] Example 1 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0064] S1. 113 mL of deionized water, 45 mL of anhydrous ethanol, and 9.6 g (0.046 mol) of tetraethyl orthosilicate (TEOS) were mixed and ultrasonicated for 30 min, and then 1.2 g (0.0427 mol) of silicon powder (D50 particle size is 0.05 μm) was added. After ultrasonication for 30 min, the pH of the system was adjusted to 8 with ammonia water (NH3·H2O), and then the mixture was placed in a 35°C water bath and stirred at a constant temperature until the water was evaporated. The evaporated sample was vacuum dried at 80°C for 12 h to obtain a SiO2@Si precursor. The SiO2@Si precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and it was kept at 1000°C for 3 h, and naturally cooled to room temperature to obtain SiO@Si particles;
[0065] S2. Take 45 mL of anhydrous ethanol solution, add nitric acid to adjust the pH to 4.5, then add 3.5 mL of tetrabutyl titanate and 2.91 g of SiO@Si particles to anhydrous ethanol, stir evenly to obtain a mixture A; take another 0.3 mL of water and 15 mL of anhydrous ethanol to prepare a mixed solution B and place it in a separatory funnel; add the mixed solution B dropwise to the mixture A while stirring, and continue stirring for 2 hours after the addition is completed, seal and age for 24 hours to prepare a TiO2@SiO@Si precursor sol, centrifuge, and vacuum dry at 70°C for 12 hours to obtain a TiO2@SiO@Si precursor;
[0066] S3. 0.08 g GO was dispersed in 20 mL deionized water and ultrasonically treated for 1 h to obtain a GO dispersion with uniform exfoliation (concentration of 4 mg / mL). Subsequently, 8 g TiO2@SiO@Si precursor and 0.12 g ascorbic acid were added to the GO dispersion and stirred for 2 h to obtain a uniform suspension. The suspension was transferred to a Teflon-lined stainless steel autoclave and reacted at 120 °C for 6 h to obtain a TiO2@SiO@Si / RGO hydrogel precursor. The hydrogel precursor was immersed in deionized water and alcohol for dialyzation to remove impurities and freeze-dried to obtain a TiO2@SiO@Si / RGO aerogel precursor. The obtained TiO2@SiO@Si / RGO aerogel precursor was placed in a sintering furnace, argon was introduced at high temperature, and the aerogel was kept at 450 °C for 1 h. The aerogel was naturally cooled to room temperature to obtain a TiO2@SiO@Si / RGO silicon-based negative electrode material, in which the mass fraction of TiO2 was approximately 21 wt%.
[0067] Depend on Figure 1 From the SEM image, we can see that the TiO2@SiO@Si / RGO silicon-based negative electrode material has a three-dimensional skeleton structure. Figure 2 From the TEM image, we can see that, as shown in the circle, there are some particles evenly distributed on the RGO. These particles are TiO2@SiO@Si particles, indicating the successful preparation of TiO2@SiO@Si / RGO silicon-based negative electrode materials. Figure 3 It can be seen from the TEM image that TiO2@SiO@Si has a double-layer coating structure.
[0068] Example 2 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0069] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of silicon powder (D50 particle size of 0.05 μm) used in step S1 was 1.1 g (0.039 mol), and the other conditions were the same as those in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was approximately 21 wt%.
[0070] Example 3 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0071] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of silicon powder (D50 particle size of 0.05 μm) in step S1 was 1.15 g (0.041 mol), and the amount of SiO@Si particles in step S2 was 1.89 g, and the other conditions were the same as in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was approximately 21 wt%.
[0072] Example 4 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0073] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S3, 0.12 g GO was dispersed in 20 mL deionized water (concentration was 6 mg / mL), the amount of ascorbic acid was 0.3 g (reducing agent: GO=2.5), and the other conditions were the same as in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was about 21 wt%.
[0074] Example 5 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0075] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that in step S3, 0.05 g GO was dispersed in 20 mL deionized water (concentration was 2.5 mg / mL), 0.01 g ascorbic acid (reducing agent: GO=0.2), and the other conditions were the same as in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was about 21 wt%.
[0076] Example 6 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0077] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of tetrabutyl titanate used in step S2 was 3.1 mL, and the other conditions were the same as in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was approximately 19 wt%.
[0078] Example 7 Preparation of TiO2@SiO@Si / RGO silicon-based negative electrode material
[0079] The TiO2@SiO@Si / RGO silicon-based negative electrode material was prepared according to the method of Example 1, except that the amount of tetrabutyl titanate used in step S2 was 4.0 mL, and the other conditions were the same as in Example 1, thereby preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material, wherein the mass fraction of TiO2 was approximately 23.6 wt%.
[0080] Comparative Example 1 Preparation of reference silicon-based negative electrode material
[0081] 113 mL of deionized water, 45 mL of anhydrous ethanol, and 9.6 g of tetraethyl orthosilicate (TEOS) were mixed and ultrasonicated for 30 min, and 1.15 g (0.041 mol) of silicon powder (D50 particle size of 0.05 μm) was added. After ultrasonication for 30 min, the pH of the system was adjusted to 8 with ammonia water (NH3·H2O). The above mixture was placed in a 35°C water bath and stirred at a constant temperature until the water was evaporated. The evaporated sample was vacuum dried at 80°C for 12 h to obtain a SiO2@Si precursor. The SiO2@Si precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and it was kept warm at 1000°C for 3 h, and naturally cooled to room temperature to obtain SiO@Si particles.
[0082] Comparative Example 2 Preparation of reference silicon-based negative electrode material
[0083] S1. 113 mL of deionized water, 45 mL of anhydrous ethanol, and 9.6 g (0.046 mol) of tetraethyl orthosilicate (TEOS) were mixed and ultrasonicated for 30 min, and then 1.15 g (0.041 mol) of silicon powder (D50 particle size is 0.05 μm) was added. After ultrasonication for 30 min, the pH of the system was adjusted to 8 with ammonia water (NH3·H2O), and then the mixture was placed in a 35°C water bath and stirred at a constant temperature until the water was evaporated. The evaporated sample was vacuum dried at 80°C for 12 h to obtain a SiO2@Si precursor. The SiO2@Si precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the temperature was kept at 1000°C for 3 h, and then naturally cooled to room temperature to obtain SiO@Si particles;
[0084] S2. Take 45 mL of anhydrous ethanol solution, add nitric acid dropwise to adjust the pH value to 4.5, then add 3.5 mL of tetrabutyl titanate and 1.89 g of SiO@Si particles to the anhydrous ethanol, stir evenly to obtain a mixture A; take another 0.3 mL of water and 15 mL of anhydrous ethanol to prepare a mixed solution B and place it in a separatory funnel; add the mixed solution B dropwise to the mixture A while stirring, and continue stirring for 2 h after the addition is completed. Seal and age for 24 h to prepare a TiO2@SiO@Si precursor sol, centrifuge, and vacuum dry at 70°C for 12 h to obtain a TiO2@SiO@Si precursor. Place the TiO2@SiO@Si precursor in a sintering furnace, pass argon gas at high temperature, keep warm at 450°C for 1 h, and naturally cool to room temperature to obtain a TiO2@SiO@Si composite material.
[0085] Comparative Example 3 Preparation of reference silicon-based negative electrode material
[0086] S1. Take 45 mL of anhydrous ethanol solution, add nitric acid to adjust the pH to 4.5, then add 3.5 mL of tetrabutyl titanate and 2.33 g of silicon powder (D50 particle size is 0.05 μm) to anhydrous ethanol, stir evenly to obtain a mixture A; take another 0.3 mL of water and 15 mL of anhydrous ethanol to prepare a mixed solution B and place it in a separatory funnel; add the mixed solution B dropwise to the mixture A while stirring, continue stirring for 2 hours after the addition is completed, seal and age for 24 hours to prepare a TiO2@Si precursor sol, centrifuge, and vacuum dry at 70°C for 12 hours to obtain a TiO2@Si precursor;
[0087] S2. 0.08 g GO was dispersed in 20 mL deionized water and ultrasonically treated for 1 h to obtain a GO dispersion with uniform exfoliation. Subsequently, 8 g TiO2@Si precursor and 0.12 g ascorbic acid were added to the GO dispersion and stirred for 2 h to obtain a uniform suspension. The suspension was transferred to a Teflon-lined stainless steel autoclave and reacted at 120 °C for 6 h to obtain a TiO2@Si / RGO hydrogel precursor. The hydrogel precursor was immersed in deionized water and alcohol for dialyzation to remove impurities and freeze-dried to obtain a TiO2@Si / RGO aerogel precursor. The obtained TiO2@SiO@Si / RGO aerogel precursor was placed in a sintering furnace, argon was introduced at high temperature, and the suspension was kept at 450 °C for 1 h. The hydrogel precursor was naturally cooled to room temperature to obtain a TiO2@Si / RGO silicon-based negative electrode material.
[0088] Comparative Example 4 Preparation of Reference Silicon-Based Anode Material
[0089] A reference silicon-based negative electrode material was prepared according to the method of Example 3, except that silicon powder was not added in step S1, and the other conditions were the same as those of Example 1, thereby preparing a reference silicon-based negative electrode material TiO2@SiO / RGO.
[0090] Test Case
[0091] The silicon-based negative electrode material, carbon black and binder (sodium alginate) obtained in the above embodiments and comparative examples were mixed in a mass ratio of 3:1:1 to prepare a negative electrode sheet. The negative electrode sheet was assembled into a battery with a separator, a positive electrode sheet (lithium sheet) and an electrolyte (1M LiPF6 as a solute, dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) and its electrochemical performance was tested according to the following method. The results are shown in Table 1.
[0092] (1) First efficiency performance: The assembled battery is charged at a constant current of 0.1C to a cut-off voltage of 2.5V, then charged at a constant voltage to a cut-off current of 0.01C, and then discharged at a constant current of 0.1C to a cut-off voltage of 0.01V. The discharge capacity is divided by the charge capacity to obtain the first charge and discharge efficiency, referred to as the first efficiency.
[0093] (2) Rate performance: The assembled batteries were tested for first cycle charging capacity under constant current charging conditions of 0.1C and 0.5C, respectively.
[0094] (3) Cycle performance: The assembled battery was tested on a battery testing system (Blue Electric Test System) and charged and discharged 100 times at a constant current of 0.1C in the voltage range of 0.01 to 2.5V under room temperature conditions. The retention rate after 100 cycles was obtained by dividing the 100th charge capacity by the first charge capacity.
[0095] Table 1
[0096]
[0097] It can be seen from the results in Table 1 that compared with Comparative Examples 1 to 4, the TiO2@SiO@Si / RGO silicon-based negative electrode material provided by the present invention has higher first-efficiency performance, rate performance and cycle performance.
[0098] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A TiO2@SiO@Si / RGO silicon-based negative electrode material, characterized in that: The TiO2@SiO@Si / RGO silicon-based negative electrode material includes RGO with a three-dimensional skeleton structure and TiO2@SiO@Si particles composited on the RGO; the TiO2@SiO@Si particles include a Si core and a SiO layer coated on the surface of the Si core and a TiO2 layer coated on the surface of the SiO.
2. The TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 1, characterized in that: The Si core contains at least one Si particle; preferably, the D50 particle size of the Si particle is 0.05-5 μm.
3. The TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 1, characterized in that: The mass ratio of the RGO to the TiO2@SiO@Si particles is (0.5-2):
100.
4. The TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 1, characterized in that: The molar ratio of SiO to Si in the TiO2@SiO@Si particles is (0.9-1.2):1; Preferably, the mass fraction of TiO2 in the TiO2@SiO@Si particles is 20-25wt%.
5. The method for preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Silicon powder, a silicate compound, water, and an organic solvent I are mixed and treated under alkaline conditions to obtain a SiO@Si precursor material, and the SiO@Si precursor material is subjected to a first calcination treatment to obtain SiO@Si particles including a Si core and a SiO layer coated on the surface of the Si core; S2. Mixing SiO2@Si particles, titanate compounds, organic solvent II, and an acidic substance to obtain a mixture A, mixing water with the organic solvent III to obtain a solution B, and then mixing the mixture A with the solution B and performing a sol-gel reaction, and obtaining a TiO2@SiO2@Si precursor material after separation and drying; S3. The TiO2@SiO@Si precursor material, graphene oxide dispersion and reducing agent are mixed and subjected to oxidation-reduction reaction, and then the obtained TiO2@SiO@Si / RGO hydrogel precursor is freeze-dried and then the obtained TiO2@SiO@Si / RGO aerogel precursor is subjected to a second calcination treatment to obtain the TiO2@SiO@Si / RGO silicon-based negative electrode material.
6. The method for preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 5, characterized in that: In step S1, the molar ratio of the silicon powder to the silicate compound is 1:(0.9-1.2); Preferably, in step S1, the alkaline condition includes a pH of 8 to 9; Preferably, in step S2, the mass ratio of the SiO@Si particles to the titanate compound is 1:(1-1.4); Preferably, in step S2, the acidic substance is used in an amount such that the pH of the mixture A is 3 to 6; Preferably, in step S3, the mass ratio of the TiO2@SiO@Si precursor material to graphene oxide is 100:(0.5-2); Preferably, in step S3, the concentration of the graphene oxide dispersion is 2.5 to 6 mg / mL; Preferably, in step S3, the mass ratio of the graphene oxide to the reducing agent is 1:(0.2-2.5).
7. The method for preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 5, characterized in that: The conditions of the first calcination treatment include: a temperature of 900 to 1100° C. and a time of 2 to 4 hours; Preferably, the conditions of the second calcination treatment include: a temperature of 400 to 500° C. and a time of 1 to 2 hours.
8. The method for preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 5, characterized in that: The sol-gel reaction time is 1 to 3 hours; preferably, the sol-gel reaction further includes an aging step of 20 to 28 hours; preferably, the oxidation-reduction reaction conditions include: a temperature of 90 to 180° C. and a time of 6 to 12 hours.
9. The method for preparing the TiO2@SiO@Si / RGO silicon-based negative electrode material according to claim 5, characterized in that: The D50 particle size of the silicon powder is 0.05 to 5 μm; Preferably, the silicate compound is selected from at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, tetrapropyl orthosilicate and tetrabutyl orthosilicate; Preferably, the titanate compound is selected from at least one of tetraethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium isooctylate and titanium acetylacetonate; Preferably, the organic solvent I, organic solvent II and organic solvent III are each independently selected from at least one of n-butanol, isobutanol and ethanol; Preferably, the reducing agent is selected from at least one of sodium bisulphite formaldehyde, sodium sulfide, ascorbic acid, hydrogen iodide and hydroquinone.
10. Use of the TiO2@SiO@Si / RGO silicon-based negative electrode material according to any one of claims 1 to 4 in lithium-ion batteries.
Citation Information
Cited By
Negative electrode material and preparation method thereof, negative electrode slurry, negative electrode pole piece and lithium ion battery
CN119674048A
Negative electrode material, preparation method, negative electrode slurry, negative electrode sheet, and lithium-ion battery
CN119674048B